Multiscale fabrication of functional materials for regenerative medicine - Bianchi, Michele (Springer, 2011)
Regenerative medicine demands new concepts and fabrication tools to improve our common knowledge about cell-cell and cell-environment interactions. In this work, Michele Bianchi  shows that different kinds of signals, such as chemical, topographical, and electrical signals,  can be arranged in a highly-controlled way. Furthermore, Michele uses scale lengths ranging from several micrometers to a few nanometers, through the employment of unconventional fabrication techniques. For each signal, Michele chose properly designed materials and fabrication methods. The external signals are capable of controlling cell adhesion and growth, opening the way for a systematic investigation of the environmental features affecting cell behavior.